2010
DOI: 10.5194/acp-10-3443-2010
|View full text |Cite
|
Sign up to set email alerts
|

Sediment records of highly variable mercury inputs to mountain lakes in Patagonia during the past millennium

Abstract: High Hg levels in the pristine lacustrine ecosystems of the Nahuel Huapi National Park, a protected zone situated in the Andes of Northern Patagonia, Argentina, have initiated further investigations on Hg cycling and source identification. Here we report Hg records in sedimentary sequences to identify atmospheric sources during the past millennium. In addition to global transport and deposition, a potential atmospheric Hg source to be considered is the local emissions associated with volcanic activity, because… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 64 publications
1
23
1
Order By: Relevance
“…In the Kimmeridge Clay, Hg and TOC values oscillate, but do so in tandem, resulting in a linear relationship between Hg and TOC. Such a relationship is similar to that observed at a number of modern locations, where Hg/TOC ratios are low and relatively consistent, between 0.01 and 0.02 (Gerkhe et al, 2009;Liu et al, 2012;Ruiz and Tomiyasu, 2015).…”
Section: Hg Concentrations and Hg/toc Ratiossupporting
confidence: 71%
See 2 more Smart Citations
“…In the Kimmeridge Clay, Hg and TOC values oscillate, but do so in tandem, resulting in a linear relationship between Hg and TOC. Such a relationship is similar to that observed at a number of modern locations, where Hg/TOC ratios are low and relatively consistent, between 0.01 and 0.02 (Gerkhe et al, 2009;Liu et al, 2012;Ruiz and Tomiyasu, 2015).…”
Section: Hg Concentrations and Hg/toc Ratiossupporting
confidence: 71%
“…Schuster et al, 2002;Ribeiro Guevara et al, 2010). In the geological record, the first use of Hg as a proxy for volcanism was by Sanei et al (2012), who observed a Hg excursion at the Permian-Triassic boundary in the Sverdrup Basin, Canadian Arctic, which they attributed to Hg output from the emplacement of the Siberian Traps.…”
Section: Mercury As a Tracer For Distal Volcanismmentioning
confidence: 98%
See 1 more Smart Citation
“…This highlights the significant effect of vegetation on the transfer of Hg to aquatic systems. Large natural variations in the Hg content in lake sediments have been observed, suggesting influences by site-specific vegetation-and forest fire history, soil type, morphology, hydrology, and climate variability [12,[28][29][30][31][32].One option to reduce the effect of site history, soil type, morphology and hydrology differences is to investigate the long-term effects of vegetation change and landscape development in a single system using long sediment records [33]. In this study, we analysed lake sediment records from two small headwater lakes, Schurmsee and Glaswaldsee in southwest Germany.…”
mentioning
confidence: 99%
“…This highlights the significant effect of vegetation on the transfer of Hg to aquatic systems. Large natural variations in the Hg content in lake sediments have been observed, suggesting influences by site-specific vegetation-and forest fire history, soil type, morphology, hydrology, and climate variability [12,[28][29][30][31][32].…”
mentioning
confidence: 99%